Pengaruh Brand Image, Selebriti Endorse dan Label Halal Terhadap Keputusan Pembelian Dengan Kepuasan Pelanggan Sebagai Variabel Intervening (Studi Kasus Konsumen Luwak White Koffie di Kab. Semarang) - Hasan Saputra, Fendi; Nabila, Rifda (EKONOMI DAN BISNIS DIGITAL, 2024)
This study aims to determine how the influence of brand image, celebrity endorsements, and halal labels on purchasing decisions with customer satisfaction as an intervention variable (a case study of white civet civet consumers in Semarang Regency). This research is a quantitative study using primary data with a population of all people in Kab. Semarang, which has consumed civet white coffee products. The sampling technique used purposive sampling technique, with the slovin formula which produced 100 samples with the data collection method using a questionnaire. The data were processed using the IBM SPSS statistical software version 20. Through data analysis that has been carried out it shows that: brand image has a significant positive effect on purchasing decisions, while celebrity endorsements and halal labels have no significant effect on purchasing decisions, customer satisfaction can mediate brand image on decisions purchases, while celebrity endorsements and purchase decisions cannot be mediated by customer satisfaction.